2012
DOI: 10.1128/mcb.06016-11
|View full text |Cite
|
Sign up to set email alerts
|

Retina Restored and Brain Abnormalities Ameliorated by Single-Copy Knock-In of Human NR2E1 in Null Mice

Abstract: gNr2e1 encodes a stem cell fate determinant of the mouse forebrain and retina. Abnormal regulation of this gene results in retinal, brain, and behavioral abnormalities in mice. However, little is known about the functionality of human NR2E1. We investigated this functionality using a novel knock-in humanized-mouse strain carrying a single-copy bacterial artificial chromosome (BAC). We also documented, for the first time, the expression pattern of the human BAC, using an NR2E1-lacZ reporter strain. Unexpectedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 60 publications
(122 reference statements)
1
29
0
Order By: Relevance
“…A consensus Nr2e1 binding sequence within the promoter region of its target gene has been proposed to contain AAGTCA, which has been identified in the promoters of Wnt7a, GFAP, S100b, Oct3/ 4, p21, Pax2, Plce1, and Pten [21,32,34,45,46,53,54]. Given the functional equivalence and the highly-conserved DBDs between human TLX and mouse Tlx [13,14], TLX may have the capacity to bind a similar consensus promoter sequence and suppress or activate the expression of multiple human counterparts of the identified mouse Tlx targets. In addition, a recent study using human neuroblastoma cell lines showed that human TLX, through binding the von Hippel-Lindau protein and stabilizing hydroxylated hypoxia-inducible factor, may bind the VEGF (vascular endothelial factor) promoter and induce VEGF expression to promote angiogenesis under hypoxic conditions [55].…”
Section: Tlx Expression Its Targets and Related Signal Pathwaysmentioning
confidence: 99%
See 4 more Smart Citations
“…A consensus Nr2e1 binding sequence within the promoter region of its target gene has been proposed to contain AAGTCA, which has been identified in the promoters of Wnt7a, GFAP, S100b, Oct3/ 4, p21, Pax2, Plce1, and Pten [21,32,34,45,46,53,54]. Given the functional equivalence and the highly-conserved DBDs between human TLX and mouse Tlx [13,14], TLX may have the capacity to bind a similar consensus promoter sequence and suppress or activate the expression of multiple human counterparts of the identified mouse Tlx targets. In addition, a recent study using human neuroblastoma cell lines showed that human TLX, through binding the von Hippel-Lindau protein and stabilizing hydroxylated hypoxia-inducible factor, may bind the VEGF (vascular endothelial factor) promoter and induce VEGF expression to promote angiogenesis under hypoxic conditions [55].…”
Section: Tlx Expression Its Targets and Related Signal Pathwaysmentioning
confidence: 99%
“…However, the rescue effect of human TLX on brain abnormalities and fierce behavior in Tlx-null mice suggests that human TLX has functions similar to those of mouse Tlx in normal brain development [13,14].…”
Section: Roles Of Tlx Homologues In the Regulation Of Nscs And Brain mentioning
confidence: 99%
See 3 more Smart Citations